2021
DOI: 10.1155/2021/5521503
|View full text |Cite
|
Sign up to set email alerts
|

Bu Shen Yi Sui Capsule Alleviates Neuroinflammation and Demyelination by Promoting Microglia toward M2 Polarization, Which Correlates with Changes in miR‐124 and miR‐155 in Experimental Autoimmune Encephalomyelitis

Abstract: Background. Bu Shen Yi Sui capsule (BSYS) is a traditional Chinese medicine prescription that has shown antineuroinflammatory and neuroprotective effects in treating multiple sclerosis (MS) and its animal model of experimental autoimmune encephalomyelitis (EAE). Microglia play an important role in neuroinflammation. The M1 phenotype of microglia is involved in the proinflammatory process of the disease, while the M2 phenotype plays an anti-inflammatory role. Promoting the polarization of microglia to M2 in MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…In a recent study of EAE mice, CNS microglia switched toward the M2 phenotype after BSYS (a traditional Chinese medicine) treatment. Concurrently, the upregulation of miR-124, but reduction of C/EBP-α/PU.1, were observed in vivo [43]. Thus, we assumed that miR-124 supplementation reduced C/EBP-α/PU.1 signaling, which regulated the expression of inflammatory associated genes and subsequently mediated microglial activation and polarization.…”
Section: Discussionmentioning
confidence: 76%
“…In a recent study of EAE mice, CNS microglia switched toward the M2 phenotype after BSYS (a traditional Chinese medicine) treatment. Concurrently, the upregulation of miR-124, but reduction of C/EBP-α/PU.1, were observed in vivo [43]. Thus, we assumed that miR-124 supplementation reduced C/EBP-α/PU.1 signaling, which regulated the expression of inflammatory associated genes and subsequently mediated microglial activation and polarization.…”
Section: Discussionmentioning
confidence: 76%
“…Related studies have shown that naringenin, an active ingredient in the traditional Chinese medicine orange-red, could regulate the M1/M2 phenotype of microglia through the MAPK signaling pathway and produced antineuritis effects [30]. Another related study showed that Bu Shen Yi Sui Capsule could alleviate neuroinflammation and demyelination by promoting microglia toward M2 polarization by regulating miR-124 and miR-155 in EAE [31]. Therefore, we speculated that the effective treatment of EAE by APS is likely to be through the regulation of microglia M1/M2 polarization phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody binding to the membranes was visualized by an enhanced chemiluminescence western detection system (Beyotime Biotechnology) and captured by a digital chemiluminescence scanner (C-Digit, LI-COR Biosciences, Lincoln, NE, USA). The intensities of the immunoblot bands were determined with Image Studio Version software (version 5.2, LI-COR Biosciences) (Zha et al, 2021).…”
Section: Western Blot Assaymentioning
confidence: 99%